Influence of foliar nutrients application on growth and yield of onion grown in nutrient deficient soil - Rahman, Inayat Ur; Afzal, Aftab; Ijaz, Farhana; Khan, Shajaul M; Khan, Sabaz A; Khan, Khalid; Ali, Niaz (Bangladesh Journal of Botany, 2018)
Commercially available foliar spray labeled as ‘Planto-fuel’ increased significantly (p ≤ 0.05) most of the growth traits viz., leaf length, bulb diameter (7.6 cm), bulb length (5.9 cm), leaves fresh weight/plant, neck fresh weight/plant, bulb fresh weight/plant (166.6 g) and plant fresh weight. It also produced the maximum yield (14.2 tons/ha) while the basal application of DAP significantly increased the number of leaves/plant and 2nd best results in yield whereas the lowest yield was observed through water spray. It is observed that the foliar application of micronutrients mixture in combination with nitrogen is the most suitable method to increase the onion production.